Measurement of Tourist Perception: Scale Development and Validation - Singh, Ajit Kumar; Tyagi, Pankaj Kumar; Sharma, Parikshit (International Journal of Psychosocial Rehabilitation, 2020)
Tourist perception is an important aspect of the tourism industry. Studies are there which advocates the importance of tourist perceived value and its implementation. The study aims to develop a scale for measuring tourist perception. An initial constructs and survey instrument are developed on the basis of extensive literature review. Data was collected through two different surveys from the respective sample size of 224 each. Based on the rigorous process of scale development, a six - dimension (Availability of facility, Price of tourism product, Infrastructure condition, Behavior of local people, Hotel condition, Promotion of tourism) tourists’ perception model is developed. Overall fit statistical indices depict that the estimated model is statistically significant and reproduces the sample covariance matrix reasonably well. Also, the result of this study provides several directions for further research.